Pre-malignant transformation by senescence evasion is prevented by the PERK and ATF6alpha branches of the Unfolded Protein Response. (1st December 2018) - Drullion, Claire; Marot, Guillemette; Martin, Nathalie; Desle, Julie; Saas, Laure; Salazar-Cardozo, Clara; Bouali, Fatima; Pourtier, Albin; Abbadie, Corinne; Pluquet, Olivier
Abstract: The incidence of carcinomas highly increases with age. However, the initial steps of the age-related molecular carcinogenic processes remain poorly characterized. We previously showed that normal human epidermal keratinocytes spontaneously and systematically escape from senescence to give rise to preneoplastic emerging cells through a process called post-senescence neoplastic emergence (PSNE). To identify molecular pathways involved in the switch from senescence to pre-transformation, we performed Connectivity Map analyses and DAVID functional annotations followed by hierarchical clustering and multidimensional scaling of the gene expression signature of PSNE cells. We identified endoplasmic reticulum stress related pathways as key regulators of PSNE. Invalidation by RNA interference of the UPR sensors PERK, ATF6α, but not IRE1α, delayed the occurrence of senescence when performed in pre-senescent cells, and increased the PSNE frequency when performed in already senescent cells. Conversely, endoplasmic reticulum stress inducers applied to already senescent cells decreased the frequency of PSNE. In conclusion, these results indicate that the activation of the UPR could protect from the early carcinogenic steps by senescence evasion. This opens new avenues to explore therapeutics that could be useful in decreasing the age-associated tumor incidence. Highlights: Highlights: 3–5 (85 characters including spaces) in a separate file. The UPR pathway is associated to the onset of keratinocyte senescence. The UPR pathway opposes to neoplastic transformation by senescence evasion. ER stress-inducing drugs inhibit neoplastic transformation by senescence evasion.